ANALYSIS OF FACTORS AFFECTING THE FREQUENCY OF VISITS AND THEIR IMPACT ON PURCHASE INTENTION AT XYZ MALL - Tjandra, Clarissa; Muqarrabin, Alex Maulana (Journal of Business And Entrepreneurship, 2019)
The level of expenditure centers in Indonesia continues to increase from year to year, but at the same time there has been a decline in several expenditure centers. One XYZ mall was struggling to survive amid the growth of new malls. The purpose of this study is analyze the factors that have an impact on frequency of visits and purchase intention at XYZ mall. This study uses quantitative attributes of causality, the research model uses Partial Least Squares regression with the number of respondents used as many as 102. The results of this study found that both communication/promotion and convenience have significant influence on frequency of visits, while tenant variety, internal environment and leisure mix do not. Frequency of visits is proven to have positive variations and reinforcement to mediate.